Custom-fitted compression garments enhance recovery from muscle damage in rugby players - Brown, F.; Jeffries, O.; Gissane, C.; Howatson, G.; van Someren, K.; Pedlar, C.; Myers, T.; Hill, J. A. (The Journal of Strength and Conditioning Research, 2022)
To evaluate the effects of custom-fitted compression garments (CG) on recovery from muscle damage in rugby players. Forty-five players were tested for lower-body strength, power, and indices of muscle damage before completing a damaging protocol (20 × 20-m sprints with 5-m deceleration, 100 drop jumps). Players were randomly assigned to wear either custom-fitted (CF, n = 13), or standard-sized CG (SSG, n = 16), or to receive sham ultrasound therapy (CON, n = 16) immediately after exercise. Players were retested immediately, then after 24 and 48 hours. Strength recovery was significantly different between groups (F = 2.7, p = 0.02), with only CF recovering to baseline values by 48 hours (p = 0.973). Time × condition effects were also apparent for creatine kinase activity (Chi2 = 30.4, p < 0.001) and midthigh girth (F = 3.7, p = 0.005), with faster recovery apparent in CF compared with both CON and SSG (p < 0.05). Custom-fitted CG improved strength recovery and indices of muscle damage in rugby players, compared with controls and standard-sized garments. Athletes and coaches would be advised to use appropriately fitted CG to enhance strength recovery after damaging exercise.